The Cretaceous Fossil Burmaculex antiquus Confirmed as the Earliest Known Lineage of Mosquitoes (Diptera: Culicidae) - Borkent, Art; Grimaldi, David A. (Zootaxa, 2016)
A second female of mid-Cretaceous Burmaculex antiquus Borkent & Grimaldi, preserved in 99 myo Burmese amber, and the oldest known member of the Culicidae, is described in detail. Although generally opaque and distorted, some character states are added or refined. The discovery of well-developed scales on the legs shows that this feature must now be considered a synapomorphy of both the fossil and all extant members of the family. Previously described synapomorphies and further interpretation here confirm the phylogenetic position of this fossil as the sister group to extant and all known fossil Culicidae. It is placed in the new subfamily Burmaculicinae.